Sublethal effects of the herbicides atrazine and glyphosate at environmentally relevant concentrations on South American catfish (Rhamdia quelen) embryos - Bordin, Eduarda Roberta; Yamamoto, Flávia Yoshie [UNESP]; Mannes, Yorrannys; Munhoz, Renan César; Muelbert, Juan Ramon Esquivel; de Freitas, Adriane Martins; Cestari, Marta Margarete; Ramsdorf, Wanessa Algarte (Elsevier, 2023)
The objective of this work was to evaluate the effects following exposure (96 h) of South American catfish (R. quelen) embryos to active ingredients and commercial formulations from atrazine and glyphosate, isolated and in mixtures, at environmentally relevant concentrations. While the survival rates were not affected, sublethal effects were evidenced after exposure. The most frequent deformities were fin damage and axial and thoracic damage. The mixture of active ingredients caused an increase in SOD and GST, differing from the treatment with the mixture of commercial formulations. The activity of AChE was significantly reduced following the treatment with the active ingredient atrazine and in the mixture of active ingredients. In general, herbicide mixtures were responsible for causing more toxic effects to R. quelen embryos. Therefore, these responses showed to be suitable biomarkers of herbicides’ exposure, in addition to generating more environmentally relevant baseline data for re-stablishing safety levels of these substances in aquatic bodies.
Keywords: Biochemical biomarkers; Catfish; Ecotoxicology; Embryotoxicity; Herbicide mixtures; Pesticides